PUBLIKASI KARYA ILMIAH SEBAGAI WUJUD PENGEMBANGAN KEPROFESIAN BERLANJUTAN - Kusworo Kusworo; Purwati Yuni Rahayu; Heri Indra Gunawan (LPPM Universitas Pamulang, 2020)
Continuing professional development is one of the teacher's efforts to improve teacher competency. The ability of teachers to support competence can be implemented through the implementation of self-development, the implementation of scientific work publications, the implementation of innovative works. Based on the situation analysis, it was obtained that SMP Nurul Hidayah teachers had not been maximized in producing a scientific work in increasing professionalism as a teacher. On the basis of the analysis of a problem, a problem-solving framework is created by carrying out community service with the title of publication of scientific works as a form of continuing professional development. The purpose of this service is that teachers are expected to understand and know various types of scientific work publications that can be utilized and maximized by the teacher. The method of community service is done by way of workshops. The results of community service conducted with the target of Nurul Hidayah Middle School teachers, Bojongsari Depok, that the teachers have understood the types of scientific publications, were seen during the question and answer session between the speaker and the service participants. The follow-up of this service is the implementation of further services that have an impact on increasing the ability to produce scientific work.Keywords: publication, scientific work, continuing professional development